Effect of weeding management on the performance of local maize populations - Peña-Asin, J.; Costar, A.; Alvarez, A. (Spanish Journal of Agricultural Research, 2013)
One of the most important stress factors in maize (Zea mays L.) fields is weed competition, which reduces the crop yield. Weeds chiefly interfere with maize and establish considerable competition for light, water and nutrients. To avoid these harmful effects, there are different agronomic measures and factors among which, the most relevant are the interactions between crop and weed, weed management practices and type of germplasm. This study attempts to evaluate maize germplasm for tolerance to weed competition in order to achieve competitive ability and suitability for farming. Ten genotypes of maize, classified into two groups, i.e. improved populations and traditional cultivars, were grown under four types of weed management practices (mechanical harrowing control, chemical control, combination of harrowing and chemical control and untreated control as check) for three years (from 2009 to 2011) in Zaragoza (Spain). We found that the effect of weed management practices was not significantly different, whereas the genotype effect was highly significant, with genotype EZS34 (mean yield of 7.7 Mg ha-1) showing the highest yield. Other traits, such as earliness, displayed a good behaviour under weed competition. On the other hand, harrowing management proved to be the most effective method of weed control although it did not show a significant response. The best results are associated with some maize genotypes that have a specific adaptation to local conditions, according to their genetic background.